Dosimetric Evaluation of 3-Dimensional Conformal Radiotherapy Technique in Postoperative Patients with Gastric Carcinoma: When Is IMRT Really Needed? - Rakesh Kapoor; Srinivasa GY; Namrata Das; Chinna Babu Dracham; Divya Khosla; Arun S Oinam (Asian Pacific Journal of Cancer Care, 2020)
Background and purpose: Adjuvant Chemoradiotherapy is the standard of care for postoperative gastric cancers with high risk features. The purpose of the current study is to do a dosimetric analysis in the postoperative setting by using 3-Dimensional Conformal Radiotherapy (3D-CRT) to a total dose of 45 Gy in 25 fractions over 5 weeks. A subsequent comparison with the 3D-CRT and IMRT of other published data is presented. Materials and Methods: Sixty postoperative patients who underwent radiation with 3D-CRT technique were included in this analysis. All patients received concurrent 5-Flurouracil or Capecitabine chemotherapy along with radiation. Radiation plans were analysed in terms of PTV coverage, conformity index (CI), homogeneity index (HI), organs at risk (OARs) and dose volume histogram (DVH) parameters. Results: DVH statistics for PTV: Dmean was 45.2±0.8 Gy, D98 was 42.9 ±1 Gy, D95 was 43.4±0.8 Gy, and D2 was 47.7±1.1 Gy. Mean CI for all plans was 1.23±0.43 and HI was 1.09±0.03. DVH parameters for OARs: right kidney, Dmean = 11.9±5.1 Gy, V18 was 21.5±13.8%, V15 was 27.2±14.9% and left kidney, Dmean was 17.7±5.8 Gy, V18 was 33.5±13.8%, V15 was 43.2±15.5%. Dmean for liver was 27.7±6.4 Gy and V20 was 69.2±15.8%. D195cc for the bowel bag was 36.3±10.8 Gy. Conclusion: The results of this study and subsequent comparison with existing literature suggests that 3D-CRT provides adequate homogenous target volume dose coverage and OAR protection, comparable to IMRT. More than the radiotherapy technique, it was the anastomotic site and the tumor location that determined the OAR doses.